2020
DOI: 10.2147/idr.s255489
|View full text |Cite
|
Sign up to set email alerts
|

<p>Tryptophol Coating Reduces Catheter-Related Cerebral and Pulmonary Infections by <em>Scedosporium apiospermum</em></p>

Abstract: Introduction: Central venous catheter (CVC) is a medical device that is used to administer medication for a long duration. Colonization by an emerging opportunistic pathogen Scedosporium apiospermum in the CVC lumen is frequently reported to cause severe complications in patients. Here, we describe the effect of fungal quorum-sensing molecule (QSM) known as tryptophol (TOH) to control S. apiospermum colonization in catheter tube lumens in both in vitro and in vivo models. Methods: Antifungal susceptibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…In the present study, we found that treatment of TOH lessened the growth of S. apiospermum CBS 117410 in a concentration-dependent manner. In consistent with our previous reports, we found that a moderate concentration (100 μM) of TOH remarkably lessened the growth of S. apiospermum ( 7 ). Although the drug of choice for S. apiospermum infections is VOZ( 39 ), we found that TOH appeared to be as effective as VOZ.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we found that treatment of TOH lessened the growth of S. apiospermum CBS 117410 in a concentration-dependent manner. In consistent with our previous reports, we found that a moderate concentration (100 μM) of TOH remarkably lessened the growth of S. apiospermum ( 7 ). Although the drug of choice for S. apiospermum infections is VOZ( 39 ), we found that TOH appeared to be as effective as VOZ.…”
Section: Discussionsupporting
confidence: 93%
“…Antifungal activity of TOH against S. apiospermum CBS 117410 was evaluated using the agar spot assay according to Kitisin et al . ( 7 ). Ten µL of S. apiospermum CBS 117410 conidia (concentration about 1 × 10 5 conidia/mL) were spotted on the surface of SDA plates containing either 10, 100, or 1000 µM of TOH or voriconazole (VOZ; Sigma-Aldrich Inc., St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation